2009
DOI: 10.1590/s0004-282x2009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Parkinson's disease

Abstract: -Pain may precede the diagnosis in Parkinson's disease (PD). The goal of this study was to assess the pain in a group of 20 females and 30 males with PD, after excluding co-morbidities as causes. It was used the following tools: Unified Parkinson's Disease Rating Scale, McGill questionnaire and Beck Depression Inventory. In 27 patients (54%), the pain was associated with PD, occurring in 22 (44%) in the off period and 5 (10%) in both on and off periods. The off period resulted in an increased frequency of pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
13
0
3
Order By: Relevance
“…NMS are thought to be present from the early stages of the disease and may be related to extension of Lewy pathology to the nondopaminergic neuronal pathway [38]. Chronic pain (CP) is one of the most frequent NMS, and it was found that 62% of a cohort of 450 PD patients had CP [20,27]. Mechanisms involved in pain symptoms and their relation to nigrostriatal dopaminergic insufficiency and motor impairment are still poorly understood [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…NMS are thought to be present from the early stages of the disease and may be related to extension of Lewy pathology to the nondopaminergic neuronal pathway [38]. Chronic pain (CP) is one of the most frequent NMS, and it was found that 62% of a cohort of 450 PD patients had CP [20,27]. Mechanisms involved in pain symptoms and their relation to nigrostriatal dopaminergic insufficiency and motor impairment are still poorly understood [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of patients in this study were in HY stage III and in the trembling group; however they were not correlated to the pain symptom. Similarly, the HY scale was not correlated to pain, probably because the vast majority of patients were in stages 2 and 2.5, representing minimally disabling stages 3 . Pain location in the 24 patients indicates as specific area with more frequent pain complaints the lumbar spine, followed by shoulder and arm.…”
Section: Discussionmentioning
confidence: 97%
“…Primary sensory disorders are described by 40 to 50% of PD patients and encompass numbness, tingling, burning, cold, heat and pain 2 . Most recurrent pain is pain in the limb affected for the longest time by motor PD symptoms 3 , being referred by approximately 30 to 50% of patients 4 . Some pain scales are very well known: visual analog scale (VAS), visual numeric scale (VNS) and pain scale represented by facial expressions, which are unidimensional tools to quantify pain intensity and severity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that positive relation had been found between PD pain and sex, age, depression, and disease severity [27, 28], but the converse results are also reported [29, 30]. In order to exclude the influence of clinical factors on pain, we applied age, sex, onset age of PD, duration of disease, duration of L-Dopa medication, and UPDRS as covariates when statistic analysis was performed on COMT polymorphisms.…”
Section: Discussionmentioning
confidence: 99%